(Invited) Characteristics of Several High-k Gate Insulators for GaN Power Device. (3rd July 2019) - Nabatame, Toshihide; Maeda, Erika; Inoue, Mari; Hirose, Masafumi; Kiyono, Hajime; Irokawa, Yoshihiro; Shiozaki, Koji; Koide, Yasuo
Abstract : We systematically investigated characteristics of Pt-gated capacitors with four kinds of gate insulators such as Hf0.57 Si0.43 Ox, Hf0.64 Si0.36 Ox, HfO2, and Al2 O3 . The Hf0.64 Si0.36 Ox films fabricated by post-deposition annealing (PDA) at 800°C in O2 (PDO), N2 (PDN), and 3% H2 (PDH) ambient exhibited quite different characteristics. After PDO, the Hf0.64 Si0.36 Ox film was partially crystallized and had a thick interfacial layer at the n-GaN/Hf0.64 Si0.36 Ox interface, while the Hf0.64 Si0.36 Ox films after PDN and PDH maintained an amorphous structure. The PDH capacitor exhibited an order of magnitude larger interface state density than the PDN capacitor, indicating that the PDN process can produce superior Hf0.64 Si0.36 Ox film. The Hf0.57 Si0.43 Ox, Hf0.64 Si0.36 Ox, HfO2, and Al2 O3 films after PDA at 800°C in N2 were 15.4, 15.9, 17.6, and 9, respectively. The HfO2 and Al2 O3 films consist of polycrystalline structure while the Hf0.57 Si0.43 Ox and Hf0.64 Si0.36 Ox films maintain an amorphous structure. The different structure strongly affected to electrical properties. The Hf0.57 Si0.43 Ox and Hf0.64 Si0.36 Ox capacitors showed superior electrical properties such as a minimal flatband voltage ( V fb ) hysteresis ( ≤ +70 mV) and a small V fb shift ( ≤ -0.46 V), as well asa low interface state density (~ 3 × 10 11 cm -2 eV -1 at -0.45 eV fromconduction band), and a high breakdown electric field ( ≥ 8.6 MV/cm) compared to those of the HfO2 and Al2 O3 capacitors.